Locally Advanced Adenoid Cystic Carcinoma of the Trachea Treated with Combined Radiotherapy and Chemotherapy - Morais, Diego Chaves Rezende (2013)
Introduction: Adenoid cystic carcinoma is the second most frequent histological type among the rare tumors of the trachea. Case report: A patient, 67 years old, with progressive dyspnea. Chest tomography showed an expansive formation in the distal third of the trachea, whose biopsy revealed adenoid cystic carcinoma of the trachea. The patient developed worsening respiratory symptoms and was referred on an emergency basis for radiotherapy with concurrent cisplatin chemotherapy with significant respiratory improvement. Two years and ten months after treatment completion, the patient showed normal respiration without relevant clinical complaints and without chronic toxicity associated with the treatment. Bronchoscopy and chest tomography showed no signs of tumor recurrence. Conclusion: Surgery is the main therapeutic modality for this type of neoplasm. However, for patients with unresectable tumors, radiotherapy is the main therapeutic modality and can be combined with chemotherapy. The disease has a poor prognosis, even after a complete surgical resection, presenting high rates of local and distant recurrence.